2021
DOI: 10.1016/j.rmed.2021.106387
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 antitrypsin deficiency severity and the risk of COVID-19: A Portuguese cohort

Abstract: Alpha-1 antitrypsin deficiency (AATD) is highly prevalent in Portugal. It is estimated that 1:5249 individuals have a ZZ genotype, and 1:281 have a SZ genotype [1]. Patients with AATD have recently been proposed as a susceptible population for COVID-19 and disease severity [2]. Data from an Italian registry of AATD revealed a geographical distribution of AATD similar to that of . A significant positive correlation was reported between the combined frequencies of the PI*SZ genotype in 67 countries and their rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 5 publications
(3 reference statements)
0
24
2
1
Order By: Relevance
“…The Pi*ZZ genotype was significantly associated with greater COVID-19 incidence (33.3%, p = 0.012), followed by Pi*MS (14.3%) and Pi*SZ (10.0%). Moreover, the baseline AAT levels were significantly lower in patients with COVID-19 (42.9 ± 12.1 vs. 65.5 ± 2.8 mg/dL; p = 0.012) [ 31 ].…”
Section: Aatd and Covid-19: Geographical Overlap And Data From Clinical Registriesmentioning
confidence: 99%
“…The Pi*ZZ genotype was significantly associated with greater COVID-19 incidence (33.3%, p = 0.012), followed by Pi*MS (14.3%) and Pi*SZ (10.0%). Moreover, the baseline AAT levels were significantly lower in patients with COVID-19 (42.9 ± 12.1 vs. 65.5 ± 2.8 mg/dL; p = 0.012) [ 31 ].…”
Section: Aatd and Covid-19: Geographical Overlap And Data From Clinical Registriesmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is a leading cause of death in many countries and because of that, it is of utmost importance to identify subjects susceptible to a life-threatening SARS-CoV-2 infection in order to protect them and to prioritize them in vaccination programs. Several lines of evidence suggest that individuals with alpha1-antitrypsin deficiency (AATD) may constitute such a population 1 , 2 , 3 . AATD arises due to mutations in alpha1-antitrypsin (AAT) gene and represents the most prominent genetic predisposition to chronic obstructive pulmonary disease and emphysema 4 , 5 .…”
mentioning
confidence: 99%
“…This finding is in line with their overall risk for lung-related mortality that is not substantially elevated 4 . On the other hand, individuals with severe AATD should remain cautious given that the current data are scarce and a small study from Portugal suggested an increased risk 1 .…”
mentioning
confidence: 99%
“…A statistical study based on 500,000 people shows that mild α1-Antitrypsin deficiency (AATD) genotypes were not associated with increased SARS-CoV-2 infection rates or fatalities [41] . For the lack of α1AT makes it easier to activate TMPRSS2, severe AATD patients may be susceptible to SARS-CoV-2 [42] , [43] . There have been four trials recruited or completed to test whether α1AT can be used for the treatment of COVID-19 patients [44] .…”
Section: Drugs Targeting the Sars-cov-2 Life Cyclementioning
confidence: 99%